An exploration of goal scoring strategies in an elite beach soccer tournament - Lastella, M.; Escobar, L.; Lovell, G. P.; Scanlan, A.; Ellison, E.; McGowan, L.; Guy, J. H. (Science and Medicine in Football, 2020)
Objectives: Despite the increasing popularity of beach soccer, few studies have examined goal scoring strategies during match-play. The aims of this study were to examine the different types of goals scored during an international tournament and determine what type of goals were associated with team performance.